Top-down mass spectrometry and assigning internal fragments for determining disulfide bond positions in proteins. Issue 1 (18th November 2022) - Wei, Benqian; Zenaidee, Muhammad A.; Lantz, Carter; Williams, Brad J.; Totten, Sarah; Ogorzalek Loo, Rachel R.; Loo, Joseph A.
Abstract : Internal fragments generated by top-down mass spectrometry can increase sequence coverage, localize disulfide bonds, and determine disulfide connectivity of disulfide-containing proteins. Abstract : Disulfide bonds in proteins have a substantial impact on protein structure, stability, and biological activity. Localizing disulfide bonds is critical for understanding protein folding and higher-order structure. Conventional top-down mass spectrometry (TD-MS), where only terminal fragments are assigned for disulfide-intact proteins, can access disulfide information, but suffers from low fragmentation efficiency, thereby limiting sequence coverage. Here, we show that assigning internal fragments generated from TD-MS enhances the sequence coverage of disulfide-intact proteins by 20–60% by returning information from the interior of the protein sequence, which cannot be obtained by terminal fragments alone. The inclusion of internal fragments can extend the sequence information of disulfide-intact proteins to near complete sequence coverage. Importantly, the enhanced sequence information that arise from the assignment of internal fragments can be used to determine the relative position of disulfide bonds and the exact disulfide connectivity between cysteines. The data presented here demonstrates the benefits of incorporating internal fragment analysis into the TD-MS workflow for analyzing disulfide-intact proteins, which would be valuable for characterizing biotherapeutic proteins such as monoclonal antibodies and antibody–drug conjugates.